Dental Trauma: An inside to Avulsion Teeth - Mendes PhD, Beatriz (2015)
Several studies shows that a wide range from 3-16% of dentoalveolar traumatic injuries result in avulsion. The ideal treatment for avulsion would be the reimplantation of the tooth. Thus, it is recommended to replant the tooth as quickly as possible. However, immediate repositioning of teeth is not always possible, so the choice of a suitable storage medium for maintenance of Periodontal Ligament cell viability is of extreme importance for the success of replantation. At the present article are discussed some storage medium and the results published in the international literature.